In-Vitro Effect of Combined Indole Butyric Acid (IBA) and Benzil Amino Purine (BAP) on the Planlet Growth of Jatropa curcas L. - M. Satria Fitri; Zairin Thomy; Essy Harnelly (Jurnal Natural, 2012)
Research oncombination of Indole Butyric Acid (IBA) andBenzil Amino Purine (BAP) to the shoot and root growth of physic nut (JatropacurcasL.) has been done in Biology Department Syiah Kuala Universityfrom June to Oktober 2007. This research used a complete randomized factorial design with 2 factors namely 0,01 mg/L, 0,05 mg/L, 0,1 mg/L, and0,5 mg/L)and BAP (0,5 mg/L and1,0 mg/L) with 3 timesrepeataitions. The result after 3 months showed that the combination IBA and BAP could not able to stimulate the formation of shoot and root in the tissue culture of physic nut.